Kapasitas Bioadsorpsi Bakteri Simbiosis Spons Laut Terhadap Kontaminan Logam Berat: Bio-adsorption Capacity of Marine Sponge Symbiosis Bacteria on Heavy Metal Contaminants - Anggi Angela; Ismail Marzuki (KOVALEN: Jurnal Riset Kimia, 2021)
Heavy metal pollution in the marine environment is quite high. Arsenic and Mercury are two types of dangerous heavy metals because they are toxic and are often found as components of pollution. The research objective was to determine the bio-absorption capacity and efficiency of sponge symbiotic bacteria against arsenic and mercury contaminants. The bio-absorbent material was used by two bacterial isolates, namely Bacillus licheniformis strain ATCC 9789 (Bl.6), the sponge symbiont Auletta Sp and Acinetobacter calcoaceticus strain PHCDB14 (Ac.8), the sponge symbiont Callyspongia aerizusa. The isolates were prepared through culture, then incubated 2 x 24 hours, suspension Bl.6 and Ac.8 were made, then adapted for 24 hours. Interaction with As3 + and Hg2 + contaminants with a concentration of 100 ppm in vials with time variations 0, 4, 8, 12, 16 days. The resulting interactions are extracted, concentrated, and acidified. The bio-absorption capacity and efficiency were determined based on absorption data using Atomic Absorption Spectrometry (AAS). The average efficiency of the bio-absorption of isolate Bl.6 against As3+ = 99.95%, Hg2+ = 88.49%, while isolate Ac.8 against As3+ = 99.95% and Hg2+ = 85.73%. Based on efficiency data, capacity and bio-absorption power relative to Bl.6 = Ac.8 against As3+ and Bl.6 ≥ Ac.8 contaminants to Hg2+. Isolates Bl.6 and Ac.8 adsorbed more strongly against As3+ contaminants than Hg2+.